1970
DOI: 10.1071/bi9700245
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis and Respiration by the Flag Leaf and Components of the Ear During Grain Development In Wheat

Abstract: SummaryRates of photosynthesis and dark respiration of the ears and flag leaves of three varieties of wheat grown at 21 DC under a constant light intensity of 3200 f.c. were measured by infrared gas analysis twice weekly throughout the period of grain development. Measurements were made on both the intact ears and the separated grains and ear structures, in air and in a mixture of nitrogen plus 320 p.p.m. C02. Dry weights of the grains, ears, and main stems were also determined.Photosynthesis by the grains was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
95
1
2

Year Published

1975
1975
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(106 citation statements)
references
References 20 publications
8
95
1
2
Order By: Relevance
“…We conclude that quantitatively, photosynthate derived directly from soybean pod photosynthesis is of little significance for podfilling compared to the supply of assimilate from the leaves. These results are in marked contrast to those reported for several cereals (7,8,13,14,17) in which it was concluded that the reproductive structures contribute at least 30% of the photosynthate for grain-filling. As suggested by the gas exchange data, soybean reproductive structures are capable of photosynthetic CO2 uptake from the external atmosphere as evidenced by a light-induced uptake of 1'4CO2 (Table II).…”
contrasting
confidence: 56%
See 2 more Smart Citations
“…We conclude that quantitatively, photosynthate derived directly from soybean pod photosynthesis is of little significance for podfilling compared to the supply of assimilate from the leaves. These results are in marked contrast to those reported for several cereals (7,8,13,14,17) in which it was concluded that the reproductive structures contribute at least 30% of the photosynthate for grain-filling. As suggested by the gas exchange data, soybean reproductive structures are capable of photosynthetic CO2 uptake from the external atmosphere as evidenced by a light-induced uptake of 1'4CO2 (Table II).…”
contrasting
confidence: 56%
“…Net photosynthesis in the reproductive organs of cereals such as barley (17), wheat (8,14,17), rice (7), and oats (13) is relatively high, contributing as much as 50 to 75% of the photosynthate to the grain. In contrast, in plants such as Phaseollis vulgaris (5), cotton (6), and peas (9) the photosynthetic contribution of the reproductive organs is low compared to that of the leaves.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study (Aggarwal et aL, unpublished), it was observed that the leaf 4' decreased to -2.0 MPa at flowering in irrigated wheat plants when dry matter production was at its peak and the flag leaf was most active (10,25). A similar change in water relations at flowering has also been observed in sorghum (12,24) and soybean (33).…”
mentioning
confidence: 99%
“…The rate of sucrose movement through the pools, given the grain-filling rate under these conditions of 1.94 f 0.12 mg-' of grain d-' (Fisher, 1990), was taken to be 220 nmol h-I. This assumes that sucrose makes up 75% of the dry weight entering the grain and that 20% of it is lost by respiration (Evans and Rawson, 1970;Fisher, 1990).…”
Section: Compartmental Analysismentioning
confidence: 99%